Tannin-based adhesive for protection of colonic anastomosis in the open abdomen. Issue 3 (11th February 2017) - Deng, Youming; Ren, Jianan; Chen, Guopu; Wang, Gefei; Gu, Guosheng; Li, Jieshou
Abstract: This study was aimed to evaluate the effect of tannin acid- polyethylene glycol (TP) adhesive on the wound healing process of primary colonic anastomosis in the open abdomen (OA). Adhesion strength test, degradation and hemostatic ability of TP were investigated. In a rat model, after standard colonic anastomoses, rats were divided into three groups: OA group; OA + FG (fibrin glue) group; OA + TP group. Five days after surgery, body weight, anastomotic bursting pressure (ABP), and histology of anastomotic tissue were evaluated. Performance of adhesion strength and hemostatic ability of TP was better than that of FG. The weight of TP decreased by over 50% after 11-day incubation. All rats survived well after surgery. Compared to OA group and OA + FG group, OA + TP group showed a significant improvement in body weight, ABP and healing state. Application of TP adhesive, used as an auxiliary treatment of colonic anastomosis operation, improved the wound strength and promoted the anastomotic healing after OA.